Lipoxin A4, a 5-lipoxygenase pathway metabolite, modulates immune response during acute respiratory tularemia. Issue 2 (14th September 2016) - Singh, Anju; Rahman, Tabassum; Bartiss, Rose; Arabshahi, Alireza; Prasain, Jeevan; Barnes, Stephen; Musteata, Florin Marcel; Sellati, Timothy J
Abstract: Respiratory infection with Francisella tularensis ( Ft ) is characterized by a muted, acute host response, followed by sepsis-like syndrome that results in death. Infection with Ft establishes a principally anti-inflammatory environment that subverts host-cell death programs to facilitate pathogen replication. Although the role of cytokines has been explored extensively, the role of eicosanoids in tularemia pathogenesis is not fully understood. Given that lipoxin A4 (LXA4 ) has anti-inflammatory properties, we investigated whether this lipid mediator affects host responses manifested early during infection. The addition of exogenous LXA4 inhibits PGE2 release by Ft- infected murine monocytes in vitro and diminishes apoptotic cell death. Tularemia pathogenesis was characterized in 5-lipoxygenase-deficient (Alox5 −/− ) mice that are incapable of generating LXA4 . Increased release of proinflammatory cytokines and chemokines, as well as increased apoptosis, was observed in Alox5 −/− mice as compared with their wild-type counterparts. Alox5 −/− mice also exhibited elevated recruitment of neutrophils during the early phase of infection and increased resistance to lethal challenge. Conversely, administration of exogenous LXA4 to Alox5 −/− mice made them more susceptible to infection thus mimicking wild-type animals. Taken together, our results suggest that 5-LO activity is a critical regulator of immunopathology observed during the acute phase of respiratory tularemia, regulating bacterial burden and neutrophil recruitment and production of proinflammatory modulators and increasing morbidity and mortality. These studies identify a detrimental role for the 5-LO–derived lipid mediator LXA4 in Ft -induced immunopathology. Targeting this pathway may have therapeutic benefit as an adjunct to treatment with antibiotics and conventional antimicrobial peptides, which often have limited efficacy against intracellular bacteria.